KELAYAKAN FLIPBOOK DIGITAL SEBAGAI MEDIA PEMBELAJARAN PADA MATERI LINGKARAN DI KELAS VIII SMP - Mutiara Saparina; Dede Suratman; Asep Nursangaji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research aimed to develop digital flipbook as an instructional medium in the Material of Circle at 8th grade of junior high school students. This was a qualitative research with Research and Development method. Subject in this research was mathematics teacher who teaching on Material of Circle at 8th grade of junior high school students, while the object was digital flipbook validity as an instructional medium in the Material of Circle at 8th grade of junior high school students. The application was used to develop digital flipbook is Kvisoft Flipbook Maker. The instruments were validation questionnaire and student response questionnaire. Digital flipbook validated by five validators, there are two lectures from Mathematics Education Department and three Junior High School teachers. The validity result revealed that the digital flipbook was valid to be an instructional medium in the Material of Circle at 8th grade of junior high school. The analysis data from digital flipbook validation got RTVTK = 3,67 categorized as ‘valid’. It got positive response from student, the average is 87.09% categorized as ‘very strong’. Keyword: Circle, Digital Flipbook, Student Response, Validity.